Zoë bakes cookies : everything you need to know to make your favorite cookies and bars - François, Zoë (Ten Speed Press, 2024)
"The expert baker and bestselling author behind Zoë Bakes Cakes and Zoë Bakes on the Magnolia Network takes us through her life with cookies and bars from her Vermont roots and Midwestern living"--